2011
DOI: 10.1002/ps.2227
|View full text |Cite
|
Sign up to set email alerts
|

Baseline susceptibilities of B‐ and Q‐biotype Bemisia tabaci to anthranilic diamides in Arizona

Abstract: These results indicate the absence of cross-resistance between the two anthranilic diamides and the currently used neonicotinoids and pyriproxyfen. Future variation in susceptibility of field populations to chlorantraniliprole and cyantraniliprole could be documented according to the baseline susceptibility range of the populations tested in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
61
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 41 publications
9
61
0
1
Order By: Relevance
“…This step is considered key and a methodology upgrade that was incorporated later in this study to standardize amount of insecticide absorbed by each of the plants in the experiment. Similar results were found, using the same bioassay method, in a parallel study carried out at the University of Arizona, which was part of the team to develop baseline susceptibility data to chlorantraniliprole and cyantraniliprole (Li et al 2012). The LC 50 value in the present study, using the stabilization period, for the susceptible laboratory colony was of 0.182 mg ai L -1 compared to 0.179 mg ai L -1 reported by University of Arizona (Li et al 2012) (Table 1).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This step is considered key and a methodology upgrade that was incorporated later in this study to standardize amount of insecticide absorbed by each of the plants in the experiment. Similar results were found, using the same bioassay method, in a parallel study carried out at the University of Arizona, which was part of the team to develop baseline susceptibility data to chlorantraniliprole and cyantraniliprole (Li et al 2012). The LC 50 value in the present study, using the stabilization period, for the susceptible laboratory colony was of 0.182 mg ai L -1 compared to 0.179 mg ai L -1 reported by University of Arizona (Li et al 2012) (Table 1).…”
Section: Discussionsupporting
confidence: 74%
“…The bioassay is a modification of the EARML method developed for the insect growth regulator buprofezin and was the same used to develop baseline susceptibility data for anthranilic diamides (Cahill et al 1996c;Li et al 2012;Caballero et al 2013). Ten to 14 whitefly adults of unknown age and gender were aspirated and transferred to clip-cages (2 cm diam, 1 cm high) on the abaxial surface of the true leaf.…”
Section: Systemic Bioassaymentioning
confidence: 99%
“…Their use has, to some extent, reduced the need for broadcast applications of insecticides to ensure stand establishment, thus lowering pesticide exposure for non-target organisms (Hull and Beers 1985;Albajes et al 2003;Cloyd and Bethke 2011). However, research has shown that seed treatments may also pose a risk to beneficial organisms via less obvious routes of exposure, causing both lethal and sublethal effects (Li et al 2012). Sublethal effects, in particular, are easily overlooked and yet may have considerable impact on natural enemy population dynamics and the level of ecosystem services contributed by these insects (Desneux et al 2007;He et al 2012;Biondi et al 2012a;Biondi et al 2013;Planes et al 2013) Systemic insecticides are characterized by low lipophilicity, typically exhibiting an octanol-water partition coefficient (log Poct) below 40 (Cloyd and Bethke 2011) which facilitates their translocation in plant tissues.…”
mentioning
confidence: 99%
“…This property facilitates their translocation in plant tissues, and may lead to contamination of pollen, floral and EFN (Maienfisch et al 2001;Lahm et al 2009) that, in turn, can cause both lethal and sublethal effects on natural enemies over potentially 4 prolonged periods (Lundgren 2009;Li et al 2012). EFN is produced in much earlier stages of plant development than floral nectar and thus has the potential to bear higher concentrations of systemic insecticides applied as seed treatments.…”
mentioning
confidence: 99%